1985
DOI: 10.1097/00004714-198510000-00023
|View full text |Cite
|
Sign up to set email alerts
|

d-Fenfluramine selectively suppresses carbohydrate snacking by obese subjects

Abstract: Twenty obese inpatients who claimed to crave carbohydrate-rich foods were given d-fenfluramine f 15 mg P.o., twice daily) or its placebo, double-blind, for two consecutive eight-day periods. Food choices were measured on treatment days 1, 7, and 8 by giving the subjects access to unlimited portions of six isocaloric meal foods (three high in carbohydrate and three high in protein) and of 10 isocaloric snack foods (five high in protein and five high in carbohydrate) available 24 hours a day in a computerized ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
31
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 3 publications
3
31
0
Order By: Relevance
“…Administration of FL or DF to animals given access to isoenergetic diets diff ering in protein and CHO contents decreased the consumption of onl y the high CHO diet (Cangiano et al 1992;Hill and Blun dell 1986;Luo and Li 1991;Wurtman and Wurtman 1979). Similarly, DF administration to CHO cravers (Wurtman et al 1985;Wurtman et al 1987), women with Late Luteal Dysphoric Syndrome (Brzezinski et al 1990), and individuals going through smoking with drawal selectively suppressed CHO but not protein in take. Although measured subjectively, the decreased appetite for CHO-rich foods previously reported by sub jects treated with FL provides additional evidence of the participation of serotonin in controlling CHO in take (Ferguson and Feighner 1987).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Administration of FL or DF to animals given access to isoenergetic diets diff ering in protein and CHO contents decreased the consumption of onl y the high CHO diet (Cangiano et al 1992;Hill and Blun dell 1986;Luo and Li 1991;Wurtman and Wurtman 1979). Similarly, DF administration to CHO cravers (Wurtman et al 1985;Wurtman et al 1987), women with Late Luteal Dysphoric Syndrome (Brzezinski et al 1990), and individuals going through smoking with drawal selectively suppressed CHO but not protein in take. Although measured subjectively, the decreased appetite for CHO-rich foods previously reported by sub jects treated with FL provides additional evidence of the participation of serotonin in controlling CHO in take (Ferguson and Feighner 1987).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that weight loss following treatment with serotoninergic drugs may relate to a selective decrease in CRO appetite. [Neuropsychopharmacology 9:201-210, 1993] brain neurotransrnission by blocking brain serotonin reuptake; OF through its metabolite, nordexfenflura mine, also releases serotonin into synapses.It has been suggested that the weight loss produced by these drugs may be related to their effect in spe ciftcally decreasing the excessive intake of CHO-rich foods (Wurtman et al 1985;Ferguson and Feighner 1987). Because such foods are usually rich in fat, reduc ing CHO intake can account for a substantial reduction in total calorie intake (Wurtman et al 1985;Ferguson and Feighner 1987).…”
mentioning
confidence: 99%
See 3 more Smart Citations